P602 Achievement of stringent histologic and composite endpoints in subjects with moderately to severely active ulcerative colitis treated with etrasimod: a post hoc analysis of the phase 3 ELEVATE UC 52 and ELEVATE UC 12 trials. (30th January 2023) - Magro, F; Peyrin-Biroulet, L; Sands, B E; Danese, S; Jairath, V; Goetsch, M; Bhattacharjee, A; Wu, J; Ferreira Branquinho, D; Modesto, I; Feagan, B G
Abstract: Background: In ulcerative colitis (UC), persistent histological activity is associated with higher rates of relapse and long-term complications, even when endoscopic remission is achieved; therefore, histological healing is a potentially important treatment target. Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator for the treatment of moderately to severely active UC. This post hoc analysis of the phase 3 ELEVATE programme evaluated the efficacy of etrasimod according to different histologic and composite endpoints. Methods: In ELEVATE UC 52 (NCT03945188) and ELEVATE UC 12 (NCT03996369), subjects (16-80 years) with moderately to severely active UC were randomised 2:1 to once-daily etrasimod 2 mg or placebo (PBO). ELEVATE UC 52 utilized a treat-through design comprising a 12-week induction period followed by a 40-week maintenance period. ELEVATE UC 12 comprised a 12-week induction period. A key secondary endpoint was the achievement of endoscopic improvement-histologic remission (EIHR). In this post hoc analysis (baseline MMS 5-9), efficacy of etrasimod was compared to PBO at weeks 12 and 52 in ELEVATE UC 52 and week 12 in ELEVATE UC 12 using additional histologic and composite endpoints defined in Table 1. Results: At week 12 and at week 52, significant improvements with etrasimod were observed in histologic outcomes, including EIHR (with and without eosinophils), histologic remission, histologic-endoscopic mucosal improvement (HEMI), endoscopic normalization-histologic remission (with and without eosinophils), and disease clearance (Figure 1). In both studies, etrasimod was superior to PBO in achievement of HEMI at week 12 (ELEVATE UC 52 and UC 12: 27.7% vs 8.9%, and 25.7% vs 10.7%, both P <0.001) and at week 52 (ELEVATE UC 52: 32.8% vs 8.9%; P <0.001). Etrasimod was also superior to PBO in achievement of histologic remission at week 12 (33.9% vs 9.6%) and at week 52 (30.7% vs 14.1%, both P< 0.001) in ELEVATE UC 52, but not ELEVATE UC 12. Etrasimod was superior to PBO using the more stringent endpoints of endoscopic normalization-histologic remission (week 12 ELEVATE UC 52 and UC 12: 10.6% vs 1.5%, P <0.001 and 10.4% vs 4.5%, P =0.030; week 52 ELEVATE UC 52: 18.2% vs 5.2%; P <0.001) and disease clearance (week 12 ELEVATE UC 52 and UC 12: 8.4% vs 1.5%, P <0.001 and 9.9% vs 4.5%, P =0.042; week 52 ELEVATE UC 52: 18.6% vs 3.7%; P <0.001). Conclusion: In this post hoc analysis, etrasimod was superior to PBO for achievement of stringent composite endpoints including EIHR, endoscopic normalization-histologic remission, and disease clearance in both ELEVATE UC 52 and ELEVATE UC 12.